Perspektif ekonomi sirkular dan pengaruh live music event sebagai nilai tambah terhadap minat pelanggan coffee shop di kuningan - Permana, Galih Ady (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Coffee shops are currently one of the most popular trends and have special fans. Various kinds of concepts and themes in each coffee shop have sprung up to attract consumers from various circles. The purpose of this study was to determine the extent of the influence of live music from a musical group or acoustic solo as the added value of a coffee shop process on the satisfaction of coffee shop visitors, who are currently in great demand by various groups, especially young people, and how the circular economy model perspective in this industry applies. The research method used is descriptive qualitative with data collection techniques using interviews and documentation. The results showed that holding an event, in this case, live music in a coffee shop, had a higher level of consumer satisfaction and, in this case, could increase profitability.